Cathode Properties, Average and Electronic Structures of αLi2MnO3–(1 − α)Li(Mn10/24Ni7/24Co7/24)O2 in Li-ion Batteries with TiNb2O7 Anode - Yasushi IDEMOTO; Takuma AIDA; Chiaki ISHIBASHI; Naoto KITAMURA; Yasuhiro HARADA; Norio TAKAMI (Electrochemistry)
In this study, the cathode properties of αLi2MnO3–(1 − α)Li(Mn10/24Ni7/24Co7/24)O2 (α = 0.5, 0.4) with Li metal and TiNb2O7 (TNO) as the negative electrode and the average and electronic structures after five charge–discharge cycles were investigated using neutron diffraction and synchrotron X-ray diffraction data. Charge–discharge tests of αLi2MnO3–(1 − α)Li(Mn10/24Ni7/24Co7/24)O2 (α = 0.5, 0.4)//Li and TNO were conducted at 0.1C, and a capacity of ∼200 mAh g−1 was obtained in the range between 2.0 V and 4.8 V vs. Li/Li+ for the cell with Li. By contrast, a capacity of ∼180 mAh g−1 was obtained in the range between 0 V and 3.3 V for the cell with TNO, and the capacity increased with each cycle for approximately 15 cycles. To clarify the cause of the change in electrode characteristics, electrodes in a 5-cycle charge–discharge state were fabricated and the average structure was investigated by Rietveld analysis using neutron diffraction and synchrotron X-ray diffraction. The results of the average structure analysis showed that the transition metal migrates to the transition-metal site and that the distortion parameter for the MO6 octahedron is high after the five-cycle charge. In addition, from an electron density analysis, in αLi2MnO3–(1 − α)Li(Mn10/24Ni7/24Co7/24)O2 (α = 0.4)//Li, which showed excellent positive electrode characteristics, the difference in electron density between the pristine and charged/discharged conditions was small at the 2b site. These results indicate that the crystal structure changes between charging and discharging depending on the anode, which affects the battery properties.